GD PBIBD(2)s in incomplete split-plot x split-block type experiments - Ambroży, Katarzyna (Metodološki zvezki, 2006)
In this paper we present a method of designing a three-factor experiment with crossed and nested treatment structures. The design considered is called a split-plot split-block design. A kind of design incomplete with respect to all three factors is examined. Additionally, we consider the usefulness of group divisible partially balanced incomplete block designs with two associateclasses in planning such experiments. In modeling data obtained from them, we take into account the structure of experimental material and a four-step randomization scheme for the different kind of units. As regards the analysis of the obtained randomization model with seven strata, we adapt anapproach typical of multistratum experiments with orthogonal block structure.
Keywords: matematična statistika; statistične metode; raziskave